Hypertension and obesity moderate the relationship between beta-amyloid and cognitive decline in midlife - Clark, Lindsay R. (Alzheimers Dement, 2018)
BACKGROUND: This study tested if central obesity, hypertension, or depressive symptoms moderated the relationship between beta-amyloid (Aβ) and longitudinal cognitive performance in late middle-aged adults enriched for Alzheimer’s disease (AD) risk. METHODS: Participants (n=207; ages=40–70; 73% parental AD) in the Wisconsin Registry for Alzheimer’s Prevention study completed 3+ neuropsychological evaluations and a [(11)C]PiB PET scan or lumbar puncture. Linear mixed-effects regression models tested interactions of risk factor x Aβ x visit age on longitudinal Verbal Learning & Memory (VLM) and Speed & Flexibility (SF) factor scores. RESULTS: The relationship between Aβ and VLM decline was moderated by hypertension (χ(2)(1) = 3.85, p = .04) and obesity (χ(2)(1) = 6.12, p = .01); those with both elevated Aβ and the risk factor declined at faster rates than those with only elevated Aβ or elevated risk factors. CONCLUSION: In this cohort, hypertension and obesity moderated the relationship between Aβ and cognitive decline.